2019
DOI: 10.1159/000499192
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Resynchronization Therapy Optimization: A Comprehensive Approach

Abstract: Since the first report on biventricular pacing in 1994, cardiac resynchronization therapy (CRT) has become standard for patients with advanced heart failure (HF) and ventricular conduction delay. CRT improves myocardial function by resynchronizing myocardial contraction, which results in reverse left ventricular remodeling and improves symptoms and clinical outcomes. Despite the accelerated development of CRT device technology and its increased application in treating HF patients, almost one-third of these pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 90 publications
0
12
0
1
Order By: Relevance
“…With the rapid development of medical technology, the continuous popularization and promotion of PCI, coronary artery bypass grafting (CABG), and coronary thrombolysis technologies and drugs have brought great help to patients with ischemic cardiomyopathy [28]. But in clinical, MIRI is an unavoidable problem, which is also a problem that needs to be solved urgently in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of medical technology, the continuous popularization and promotion of PCI, coronary artery bypass grafting (CABG), and coronary thrombolysis technologies and drugs have brought great help to patients with ischemic cardiomyopathy [28]. But in clinical, MIRI is an unavoidable problem, which is also a problem that needs to be solved urgently in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…By various clinical experiments have shown that CRT improves cardiac function, as well as monolithic quality of livelihood, and decreases HF hospitalizations, health care expenses, and mortality. In spite of the stepped-up progress of CRT device technique and its enhancive application to HF patients' treatment, nearly one-third of these patients have non-respond to the remedy or gain some clinical advantages from device implantation.CRT remaining a primary challenge that faces electrophysiologists and research workers [33,34].…”
Section: Non-drug Treatment 41 Crtmentioning
confidence: 99%
“…Patients with CRT benefit from the effects of electric and mechanical synchronization of their ventricular muscle and LV function is ultimately improved. However, CRT is not effective in approximately 1/3 of the patients and this CRT non-responder issue has not been resolved to date [2,3]. Therefore, for achieving a more ubiquitous performance of CRT in patients with HF, patient-specific simulation methods for screening CRT non-responders need to be established.…”
Section: Introductionmentioning
confidence: 99%